PENGARUH KETERAMPILAN BERWIRAUSAHA TERHADAP PERTUMBUHAN USAHA BERKELANJUTAN PADA INDUSTRI KECIL DI KOTA SUKABUMI - Herwan Abdul Muhyi (Sekolah PascaSarjana Unpad, 2012)
The purposes of this research is to describe entrepreneurial skill and its influence on sustained business growth. This research expect to obtain a new concept of Business Administration Study especially on entrepreneurial skills and sustained business growth. The locus of this study is business organization (small industry) and focused on entrepreneurial skill and sustained business growth. Descriptive analyses was used to describe the condition of research object. This is a survey research which is used questionaire as basic data instrument. So, the method of this research is explanatory survey. The population size of this research is 750 small industry, and sample size is 150 small industry according to the criteria specified in the Structural Equation Modeling (SEM). The results showed that the entrepreneurship skills affect sustained business growth, this result explains that the hypothesis tested. The magnitude of the influence of entrepreneurial skills for sustained business growth of small industries in Sukabumi is significantly determined by the personal entrepreneurial skills, business management skills and technical skills. This study reinforces the concept of Hisrich, et al, Frinces, Baum, et al and Lee and Tsang about entrepreneurship skills will have a positive impact on business growth. However, this study finding that entrepreneurship skills affect sustained business growth,sustained growth mean industry grow in a time period. For entrepreneurial skill variable, the results showed that the business management skills as a dominant factor that reflected entrepreneurial skill and personal entrepreneurial is the less factor. This suggests that entrepreneurial skills can really only be learned (entrepreneur are made) not only the legacy of the inherent entrepreneurial hereditary (traditional). This study indicate for small scale industry, high entrepreneurial skill not also raise the credibility of venture to gain financing externally. It's the specified characteristic of small industry. So, supporting from government in regulation and capital is very important to get investor believes.